2021
DOI: 10.3389/fpls.2021.690231
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Mediated Targeted Mutagenesis of CYP93E2 Modulates the Triterpene Saponin Biosynthesis in Medicago truncatula

Abstract: In the Medicago genus, triterpene saponins are a group of bioactive compounds extensively studied for their different biological and pharmaceutical properties. In this work, the CRISPR/Cas9-based approach with two single-site guide RNAs was used in Medicago truncatula (barrel medic) to knock-out the CYP93E2 and CYP72A61 genes, which are responsible for the biosynthesis of soyasapogenol B, the most abundant soyasapogenol in Medicago spp. No transgenic plants carrying mutations in the target CYP72A61 gene were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 68 publications
(124 reference statements)
1
18
0
Order By: Relevance
“…Heritable genomic alterations and transgene-free plants were produced as a consequence of the targeted plant genome editing made possible by CRISPR-Cas9 ( Hu and Gao, 2023 ). Utilizing the CRISPR-Cas system several crops have shown both qualitative and quantitative gains ( Zhang et al., 2020 ; Carrijo et al., 2021 ; Confalonieri et al., 2021 ; Eid et al., 2021 ; Oz et al., 2021 ; Zhang et al., 2021 ; Biswas et al., 2022 ; Lu and Tian, 2022 ). An overview of CRISPR- Cas technological advancements are shown in Figure 2 .…”
Section: Genome Editing Tools For Crop Breedingmentioning
confidence: 99%
“…Heritable genomic alterations and transgene-free plants were produced as a consequence of the targeted plant genome editing made possible by CRISPR-Cas9 ( Hu and Gao, 2023 ). Utilizing the CRISPR-Cas system several crops have shown both qualitative and quantitative gains ( Zhang et al., 2020 ; Carrijo et al., 2021 ; Confalonieri et al., 2021 ; Eid et al., 2021 ; Oz et al., 2021 ; Zhang et al., 2021 ; Biswas et al., 2022 ; Lu and Tian, 2022 ). An overview of CRISPR- Cas technological advancements are shown in Figure 2 .…”
Section: Genome Editing Tools For Crop Breedingmentioning
confidence: 99%
“…Also, in other crops like soybean, the simultaneous CRISPR‐based editing of GmF3H1 , GmF3H2 , and GmFNSII‐1 was carried out to increase its isoflavone content and thus improve its resistance to the soybean mosaic virus (Zhang et al, 2020). In Medicago truncatula , rerouting of the saponin pathway was achieved by knocking out the MtCYP93E2 and MtCYP72A61 genes, resulting in the accumulation of hemolytic sapogenins and avoiding the accumulation of sapogenols (Confalonieri et al., 2021).…”
Section: Programmable Tools For Genome Editing and Transcriptional Re...mentioning
confidence: 99%
“… Rodas et al (2021) edited the M. truncatula SUPERMAN ( MtSUP ) gene with CRISPR/Cas 9 and determined the impairment of MtSUP function with observing defects in floral development and inflorescence architecture in mtsup mutant allel carrying plants. Confalonieri et al (2021) also used the CRISPR/Cas9 gene-editing tool to knock out the two cytochrome P 450 genes ( CYP93E2 and CYP72A61 ) that are responsible for soyasapogenol B production in Medicago spp. Their results showed that 51 putative CYP93E2 mutant plant lines with an 84% editing efficiency did not produce soyasapogenols in the leaves, stems, and roots with diverting the metabolic pathway toward the production of valuable hemolytic sapogenins.…”
Section: Applications In Legumesmentioning
confidence: 99%